Early Disease and Low Baseline Damage as Predictors of Response to Belimumab in Patients With Systemic Lupus Erythematosus in a Real‐Life Setting. Issue 8 (12th June 2020) - Gatto, Mariele; Saccon, Francesca; Zen, Margherita; Regola, Francesca; Fredi, Micaela; Andreoli, Laura; Tincani, Angela; Urban, Maria Letizia; Emmi, Giacomo; Ceccarelli, Fulvia; Conti, Fabrizio; Bortoluzzi, Alessandra; et al.
Abstract : Objective: To investigate predictors of response, remission, low disease activity, damage, and drug discontinuation in patients with systemic lupus erythematosus (SLE) who were treated with belimumab. Methods: In this retrospective study of a multicenter cohort of SLE patients who received intravenous belimumab, the proportion of patients who achieved remission, low disease activity, and treatment response according to the SLE Responder Index 4 (SRI‐4) was determined, and the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) was used to score disease damage yearly over the follow‐up. Predictors of outcomes were analyzed by multivariate logistic regression with the results expressed as odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: The study included 466 patients with active SLE from 24 Italian centers, with a median follow‐up period of 18 months (range 1–60 months). An SRI‐4 response was achieved by 49.2%, 61.3%, 69.7%, 69.6%, and 66.7% of patients at 6, 12, 24, 36, and 48 months, respectively. Baseline predictors of response at 6 months included a score of ≥10 on the SLE Disease Activity Index 2000 (SLEDAI‐2K) (OR 3.14 [95% CI 2.033–4.860]) and a disease duration of ≤2 years (OR 1.94 [95% CI 1.078‐3.473). Baseline predictors of response at 12 months included a score of ≥10 on the SLEDAI‐2K (OR 3.48 [95% CI 2.004–6.025]) and an SDI score of 0 (OR 1.74 [95% CI 1.036–2.923]). Baseline predictors of response at 24 months included a score of ≥10 on the SLEDAI‐2K (OR 4.25 [95% CI 2.018–8.940]) and a disease duration of ≤2 years (OR 3.79 [95% CI 1.039–13.52]). Baseline predictors of response at 36 months included a score of ≥10 on the SLEDAI‐2K (OR 14.59 [95% CI 3.54–59.79) and baseline status of current smoker (OR 0.19 [95% CI 0.039–0.69]). Patients who were in remission for ≥25% of the follow‐up period (44.3%) or who had low disease activity for ≥50% of the follow‐up period (66.1%) accrued significantly less damage ( P = 0.046 and P = 0.007). A baseline SDI score of 0 was an independent predictor of achieving low disease activity in ≥50% of the follow‐up period and remission in ≥25% of the follow‐up period. Our findings suggest that the lower the baseline damage, the greater the probability of achieving remission over the course of ≥25% of the follow‐up. Further, there was a negative association between the number of flares reported prior to belimumab initiation and the frequency of belimumab discontinuation due to inefficacy ( P = 0.009). Conclusion: In patients with active SLE and low damage at baseline, treatment with belimumab early in the disease may lead to favorable outcomes in a real‐life setting.